2022
DOI: 10.31817/vjas.2022.5.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Performances of Boro Rice as Affected by Different Concentrations of Marine Water

Abstract: Salinity is one of the most devastating abiotic stresses limiting crop production. Considering this issue, a pot experiment was conducted at Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during the boro season (2017-2018) using two rice(Oryza sativa L.) varieties, namely BRRI dhan28 (salt sensitive) and BRRI dhan47 (salt tolerant),to assess the effects of varied salinity levels on the growth and the performance of the rice varieties under salt stress conditions. Four salinity treatments were used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…Imposition of 2800 ppm NaCl caused death of all plant at harvesting time as a result reduction of total grains panicle −1 was 100% under this treatment. These results were in line with previous studies (Nahar et al, 2009;Islam et al, 2022) who reported that salinity decreases number of grains in rice.…”
Section: Filled Grains Panicle −1supporting
confidence: 94%
See 4 more Smart Citations
“…Imposition of 2800 ppm NaCl caused death of all plant at harvesting time as a result reduction of total grains panicle −1 was 100% under this treatment. These results were in line with previous studies (Nahar et al, 2009;Islam et al, 2022) who reported that salinity decreases number of grains in rice.…”
Section: Filled Grains Panicle −1supporting
confidence: 94%
“…Upon exposure to 2800 ppm NaCl, the plant height of rice declined by 19, 48, 71 and 100% at 40, 60 and 80 DAT, and at harvest, respectively, compared with untreated control. Our results in agreement with Islam et al (2022) who stated that salinity decreased plant height of rice and magnitude of decreases increased with the advancement of the growth period. Under saline conditions, Na + enter into shoot of rice through apoplastic pathway which disrupts cell division and cell elongation and ultimately reduced growth of rice (Hussain et al, 2017).…”
Section: Plant Heightsupporting
confidence: 93%
See 3 more Smart Citations